Factors Affecting Farming Sustainability for Farmers at Banger El-Sokar – Region – El-Behira Governorate - Mohamed, Khaled Elsayed; Sakr, Islam Hassan; Amer, Ahmed Mamdouh; Mohamed, Ebtesam Maher (Journal of agricultural, environmental and veterinary sciences, 2023)
The research aimed mainly at identifying the level of farmers' behavior related to sustainable from practices, as well as the nature of the correlation between their studied characteristics as independent variables and the level of their behavior as a dependent variable in addition estimate it the proportion of the explained variance This research suggests Extensional vision to the diffusion of sustainable farm practices among farmers., A questionnaire was designed and administered to a random sample of 172 farmers in the village of Sayedna Ayoub, Banjar region. Data analysis highlights that nine independent variables that explain 60% of the variation are sustainable practices for farmers: they include: : the size of land holding, the educational level of the respondent's family, the animal holding capacity , the standard of living of the respondent's family, ownership of agricultural machinery, sources of agricultural information, opinion leadership, cultural openness, and  geographical openness, the factor analysis indicate the importance of eight elements for formulating the idea of agricultural sustainability whose structural concept proves the degree Acceptable statistic of viability and reliability, including : Farmer's environmental behavior, Crop pattern, Integrated pest management ,  Farmer's awareness of sound irrigation  , Agricultural innovativeness , Improving farm status and conditions , Level of farmer's utilization of farm by products, Knowledge and implementation of innovations in order to overcome climate change.
Keywords: factors; sustainability; farm; farmers